Challenges Caused by Imported Cases Abroad for the Prevention and Control of COVID-19 in China - Zhu, Jianfei; Zhang, Qingqing; Jia, Chenghui; Xu, Shuonan; Lei, Jie; Chen, Jiakuan; Xia, Yanmin; Wang, Wenchen; Wang, Xuejiao; Wen, Miaomiao; Wang, Hongtao; Zhang, Zhipei; et al. (Frontiers in Medicine, 2021)
Background: Overseas imported cases of COVID-19 continue to increase in China recently, so we conducted this study to review the epidemiological characteristics of these patients. Methods: From February 26th to April 4th, 2020, the imported cases from abroad were enrolled in this study. The effect of prevention countermeasures in curbing the spread of COVID-19 was assessed in this study. Moreover, We defined incubation period and confirmed time as from the date of leaving epicenter to date of symptom onset and date of final diagnosed, respectively, the interval of symptom onset to final diagnosed time was defined as diagnostic time. Categorical variables were summarized as numbers and percentages, the difference among the variables were analyzed. Results: For 670 cases imported from abroad, 555 were Chinese, 115 were foreigners. Apparently, confirmed cases had significant decreased after China was compelled to temporarily suspend the entry of foreign passport holders with valid visas or residence permits, six days after implement of controlled measures, the daily new confirmed cases were reduced to 13 cases. Moreover, About 84.3% patients (166/197) presented symptoms one week after leaving the epicenter, notable, 7 patients (3.6%) had symptoms two weeks after leaving the epicenter, the median incubation period was 3.0 days(inter quartile range, 1.0 to 6.0), the 95th percentile was 11.6 days. Additionally, most of cases (92.9%) were detected positively of nucleic acid after symptom onset with four days, the median diagnostic time was 2.0 days, (interquartile range, 1.0 to 3.0), the 95th percentile of the distribution was 5.0 days. Finally, about 5.8% patients were healthy carriers, the median confirmed time of asymptomatic patients was 4.0 days, (interquartile range, 2.0 to 9.0). The following variables might associated with confirmed time: symptom type (P=0.005), exported regions (P＜0.001) and symptom onset time (P＜0.001). Conclusions: The prevention countermeasures for imported cases implemented by the Chinese government played an indispensable role in curbing the spread of COVID-19, the time of departure from epicenter could provide to estimate the incubation period and confirmed time, two-week quarantine period might need to be prolonged, asymptomatic patients should be closely monitored.